2011
DOI: 10.1007/s10584-011-0345-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the changes in extreme vulnerability over East Asia due to global warming

Abstract: A number of indices have been employed to describe weather extremes on the basis of climate regimes and public concerns. In this study, we combined these traditional indices into four groups according to whether they relate to warm (T warm ), cold (T cold ), wet (P wet ), or dry (P dry ) extremes. Analysis of the combined indices calculated for the daily temperatures and precipitation at 750 meteorological stations in Korea, China, and Japan for 1960s-2000s shows increasing trends in T warm and P dry events an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 25 publications
(24 reference statements)
1
15
0
Order By: Relevance
“…Temporally, over the entire South Korea domain, LGS increased by 4.5 days decade −1 through the last 27 years, mostly due to an increase in EGS dates (2.6 days decade −1 ). Overall, the lengthening of the vegetation growing season further suggests that the nationwide reforestation has responded to the recent climatic warming in South Korea [36]. Although a lengthening of the growing season during the last three decades of the 20 th century is consistent with many previous studies [37], [38], [39], [40], most of these focused mainly on the earlier spring contributions to the total growing season.…”
Section: Discussionsupporting
confidence: 83%
“…Temporally, over the entire South Korea domain, LGS increased by 4.5 days decade −1 through the last 27 years, mostly due to an increase in EGS dates (2.6 days decade −1 ). Overall, the lengthening of the vegetation growing season further suggests that the nationwide reforestation has responded to the recent climatic warming in South Korea [36]. Although a lengthening of the growing season during the last three decades of the 20 th century is consistent with many previous studies [37], [38], [39], [40], most of these focused mainly on the earlier spring contributions to the total growing season.…”
Section: Discussionsupporting
confidence: 83%
“…The climate exposure data were acquired from the climate model and hydrologic model simulations under the A1B climate change scenario. These climate data were set by downscaling the outputs from the National Center for Atmospheric Research (NCAR) Community Climate System Model 3 with the PSU/NCAR Mesoscale Model (MM5) [34,35]. The outputs from the MM5 were used to derive hydrologic models of the land-surface process model and a hydrologic simulation program in FORTRAN, which in turn provided the hydrologic data.…”
Section: Performance Valuesmentioning
confidence: 99%
“…In East Asia, the most significant increase is seen in Southeastern China under future emission scenarios (Seo et al 2014). Lee et al (2012) suggested northern East Asia will be subject to increased heat extremes. Based on a set of atmosphere-ocean coupled general circulation models from CMIP5, Yang et al (2014) indicated that warming is expected all over China, and northern China shows greater warming than southern China, especially the Tibetan region.…”
Section: Introductionmentioning
confidence: 99%